Teledermatology Use in Remote Areas of French Guiana: Experience From a Long-Running System - Messagier, Anne-Laure; Blaizot, Romain; Couppié, Pierre; Delaigue, Sophie (Frontiers in Public Health, 2019)
INTRODUCTION: French Guiana is an overseas region of France on the north coast of South America and is mostly covered by tropical rainforest. Most human settlements are located along the coast while some settlements are scattered across the hinterland. In 2001, the French public health service launched a telemedicine pilot project between the main hospital in Cayenne and remote health centers in French Guiana to tackle healthcare access inequalities. The aim of the present study was to review dermatology cases of the French Guiana telemedicine network to assess the use of telemedicine in dermatology, in order to evaluate its usefulness and propose ways to improve the system. METHODS: A retrospective study was conducted on all dermatology cases referred between July 2015 and December 2016 through the French Guiana platform. The Model for Assessment of Telemedicine (MAST) methodology was used as recommended by the European Union. RESULTS: A total of 254 cases were reviewed by dermatologists at Cayenne hospital over the 18-month study period, with a mean of 14 cases per month. All the 16 peripheral health centers used the telemedicine service during the study. In most cases (202/254, 80%), specialists provided a single diagnosis to the referrers. Infectious diseases represented the main reasons for requests (92/202, 46%) including 32% (29/92) of neglected tropical diseases like leprosy and cutaneous leishmaniasis. A total of 39% (100/258) peripheral centers answered the end-users’ survey, and more than 85% found the answer delay was fast, the service useful and with an educational benefit. Overall, the accuracy of the diagnosis increased with the quality of the pictures provided, though the latter was good in only 60% (75/125) of the cases. Most patients for whom a teleconsultations has been required (234/254, 92%) have been managed in the peripheral health centers, while referring the patient to Cayenne was necesseray for only 20/254 (8%). CONCLUSION: The telemedicine system in French Guiana appears to be an interesting solution to the lack of specialists and allowed a better access to specialized dermatology care for people living in the remote areas of this region.